Wearable technologies and wireless body sensor networks for healthcare - Velez, Fernando J.; Miyandoab, Fardin Derogarian, 1975- (The Institution of Engineering and Technology, 2019)
"Continuous advances in wearables, sensors and smart Wireless Body Area Network technologies have precipitated the development of new applications for on-, in- and body-to-body wearable communications for healthcare and sport monitoring. Progress in this cross-disciplinary field is further influenced by developments in radio communication, protocols, synchronization aspects, energy harvesting and storage solutions, and efficient processing techniques for smart antennas. This book covers various scenarios and solutions using sensor devices and systems for activity recognition and their applications, including wearable communication, smart sensing, RF propagation, and measurement. The authors illustrate conceptual aspects and applications and provide a new vision in characterizing wearable technologies and the need for interoperability. Energy harvesting within wearable solutions is a key issue addressed here as it helps increase energy efficiency and reliability in wearable antennas and sensor devices."--Provided by publisher.
Keywords: Bioengineering.; Biosensors -- Research.; Biosensors -- Technological innovations.; Body area networks (Electronics); Transducers, Biomedical.; Wireless sensor networks.; Obstetrics -- Research.; Energy harvesting.; elektronické knihy; electronic books